Immunoglobulin D myeloma: clinical features and outcome in the era of novel agents. (26th January 2014) - Zagouri, Flora; Kastritis, Efstathios; Symeonidis, Argiris S.; Giannakoulas, Nikolaos; Katodritou, Eirini; Delimpasi, Sosana; Repousis, Panagiotis; Terpos, Evangelos; Dimopoulos, Meletios A.
Abstract Objectives Immunoglobulin D (IgD) multiple myeloma is an uncommon variant of the disease probably associated with poorer prognosis. However, data on IgD myeloma patients treated in the novel agent era are lacking. Methods To assess the frequency and the specific characteristics and evaluate the outcome of patients with IgD myeloma, we analyzed the database of the Greek Myeloma Study Group. Results Between January 2000 and December 2012, among the 1239 patients with symptomatic myeloma, 31 (2.5%) were diagnosed with IgD myeloma. The median age of patients with IgD myeloma was 65 yr (range 26–80 yr) versus 68 yr (range 23–96 yr) of all others, and 84% had lambda light chain (vs. 38% of the patients with other subtypes). Patients with IgD myeloma presented more often with features of high‐risk disease, that is, with advanced ISS, high LDH, significant renal dysfunction, and large amounts of Bence Jones proteinuria. Response to primary therapy was similar to other patients, although there was a trend for better quality of responses in patients with IgD myeloma. The median survival of these patients was 51.5 months versus 50.7 months for patients of other subtypes. In a multivariate model to adjust for differences in prognostic features, IgD myeloma was not associated with a different prognosis. Conclusion The incidence of IgD myeloma is 2.5%. Although patients with IgD myeloma present more often with high‐risk features, their outcome in the era of novel agents is similar to that of patients with other myeloma subtypes.